Answer:
Step-by-shwowbfizbaasldkt fbdisjs r fbfjep explanation:
Answer:
a = 7
Step-by-step explanation:
3(1 - 2a) = -3a - 18
3 - 6a = - 3a - 18
Add 18 to each side:
3 + 18 - 6a = - 3a - 18 + 18
21 - 6a = - 3a
Add 6a to each side:
21 - 6a + 6a = - 3a + 6a
21 = 3a
3a = 21
Divide each side by 3:
3a ÷ 3 = 21 ÷ 3
a = 7
Answer:
(x-6) (2x+1)
Step-by-step explanation:
1) move everything over to the left side, so subtract 11x and 6.
2x^2 -11x - 6 = 0
2)multiply 2(a term) with -6 (c term)
x^2 -11x -12
3) factor and find what multiples to -12 and adds up to -11. in this case its -12 and positive 1
(x-12) (x+1)
4) divide -12 and 1 by the original a term (2)
(x-6) (x+1/2)
5) move the denominator of 2 over to the x.
(x-6) (2x+1)
Answer:
y ≤ x - 1
Step-by-step explanation:
The slope is 1 (every unit for x, there is a unit for y, rise/run is 1/1). The y-intercept is -1, because the line crosses the y-axis at -1. The graph is shaded below the line, and the line is solid, meaning that y is less than or equal to x -1, or y ≤ x - 1.